2018
DOI: 10.1093/ibd/izy051
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease in Inflammatory Bowel Disease: Prevalence and Risk Factors

Abstract: NAFLD is more common and occurs at a younger age in IBD than in nonIBD subjects. However, further investigation is required to ascertain possible NAFLD pathogenic IBD-related factors other than conventional/metabolic ones. 10.1093/ibd/izy051_video1izy051.video15774874877001.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 36 publications
0
74
0
Order By: Relevance
“…Factors putatively predisposing to fatty liver in IBD were found to be age, a higher BMI, and higher serum triglycerides [115]. Although disease activity, duration and prior surgery were also reported to impact on NAFLD [114], other studies did not find a close relationship with these variables instead the presence of metabolic syndrome was more closely related to liver involvement [116,117]. In the latter study, no significant differences were found between non-IBD and IBD patients when BMI was compared, but IBD patients had an 18.5% morbid abdominal circumference compared with 6.8% in patients without IBD [117].…”
Section: Comorbidities In Obesity Shared With Inflammatory Bowel Diseasementioning
confidence: 99%
“…Factors putatively predisposing to fatty liver in IBD were found to be age, a higher BMI, and higher serum triglycerides [115]. Although disease activity, duration and prior surgery were also reported to impact on NAFLD [114], other studies did not find a close relationship with these variables instead the presence of metabolic syndrome was more closely related to liver involvement [116,117]. In the latter study, no significant differences were found between non-IBD and IBD patients when BMI was compared, but IBD patients had an 18.5% morbid abdominal circumference compared with 6.8% in patients without IBD [117].…”
Section: Comorbidities In Obesity Shared With Inflammatory Bowel Diseasementioning
confidence: 99%
“…Not all of the data supports a connection between IBD severity and the development of NAFLD. Principi et al reported that disease activity was not associated with difference in NAFLD prevalence, nor was there a correlation with IBD location or behavior [6]. Non-specific serological markers of inflammation (erythrocyte sedimentation rate and C-reactive protein) were no different in IBD patients versus those with both conditions [42].…”
Section: Clinical Features Of Patients With Nafld and Ibdmentioning
confidence: 97%
“…Non-obese patients with NAFLD are more commonly younger, and less likely to have insulin resistance, diabetes or hypercholesterolemia than their overweight or obese counterparts [30]. There are several theories about the role of inflammation in the development of NAFLD and some authors propose that IBD patients are at increased risk for this condition [6]. The reported prevalence of NAFLD may be as high as 55% in patients with IBD [7][8][9].…”
Section: Prevalence Of Nafldmentioning
confidence: 99%
See 2 more Smart Citations